2017
DOI: 10.22319/rmcp.v8i2.4401
|View full text |Cite
|
Sign up to set email alerts
|

Emisión de metano en ovinos alimentados con Pennisetum purpureum y árboles que contienen taninos condensados

Abstract: Emisión de metano en ovinos alimentados con RESUMENEl objetivo fue evaluar el efecto de los taninos condensados (TC) contenidos en el follaje de arbóreas tropicales, sobre el consumo de materia seca y orgánica (CMS, CMO), la digestibilidad de la materia seca (DMS) y emisiones de metano (CH4) en ovinos alimentados con una ración basal de pasto Pennisetum purpureum. Cuatro ovinos de pelo con un peso vivo promedio de 21.6±2.0 kg se sometieron a cuatro tratamientos en un diseño cuadro latino 4 x 4. Los tratamiento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
(37 reference statements)
1
2
0
3
Order By: Relevance
“…At 48 h after incubation the inclusion of B. simaruba at 30% reduced CH4 production at 21.39 and 25.15% for IOM and DOM, respectively. This result is similar to that obtained by Piñeiro-Vázquez et al [62] when they included 30% of B. simaruba in sheep diets and concluded that the effect of CT from this species reduced CH4 emissions. However, different animal species may vary in their response to the same mitigation strategy [34] and the results obtained in the present study must be verified in a in vivo trial using cattle.…”
Section: Methane Productionsupporting
confidence: 90%
“…At 48 h after incubation the inclusion of B. simaruba at 30% reduced CH4 production at 21.39 and 25.15% for IOM and DOM, respectively. This result is similar to that obtained by Piñeiro-Vázquez et al [62] when they included 30% of B. simaruba in sheep diets and concluded that the effect of CT from this species reduced CH4 emissions. However, different animal species may vary in their response to the same mitigation strategy [34] and the results obtained in the present study must be verified in a in vivo trial using cattle.…”
Section: Methane Productionsupporting
confidence: 90%
“…The secondary effect of CT on CH 4 is the reduction in fiber digestion and fermentation, the decrease in the inter-specific transfer of hydrogens between protozoa and methanogenic archaea and the consequent increase in the concentration of propionic acid in the rumen [61]. Piñeiro-Vázquez et al [62] included 30% of B. simaruba in sheep diets and concluded that the effect of CT from this species reduced CH 4 emissions despite not observing a numerical difference, those results are similar to the ones obtained in the present investigation. However, different animal species may vary in their response to the same mitigation strategy [34] and the results obtained in the present study must be verified in a in vivo trial using cattle.…”
Section: Methane Productionmentioning
confidence: 99%
“…La pérdida de energía en forma de CH 4 tiene una importancia significativa, debido a que las dietas de los bovinos en el trópico se basan en el pastoreo gramíneas nativas y pastos naturalizados con bajo contenido de proteína cruda (<7 %), digestibilidad (<50 %) y alto contenido de carbohidratos estructurales (60-80 % FDN) (Benitez et al, 2017;Ku-Vera et al, 2013;Piñeiro-Vázquez et al, 2017). Este tipo de dietas, generan una alta proporción de ácido acético, baja producción de propionato y un aumento en la emisión de CH 4 entérico (Archimède et al, 2014).…”
Section: Potencial Para La Disminución De Ch 4 Entérico De Plantas Ar...unclassified